An efficient and economic desilitation strategy for reservoir sustainable development under the threat of extreme flooding threaten. Issue 3 (10th February 2022) - Hung, Chia-Ching; Lai, Jihn-Sung; Huang, Cheng-Chia
Abstract: Severe sediment disaster has already been observed locally and worldwide, and serious disasters will happen increasingly in the future due to climate change. Hence, developing a proper reservoir desilitation strategy is an urgent priority to ensure sustainable water resources development worldwide. This study aims to investigate the release efficiency of the bypass tunnel in the reservoir. Firstly, a 2D numerical model was adapted to reproduce the most severe sedimentation disaster due to Typhoon Aere and obtain a reliable result compared with the measured data. Then, the concept of climate change was embedded to understand the release capability of the bypass tunnel under slight to worst scenarios. Finally, the bypass tunnel is demonstrated to be effective in releasing sediment during typhoon periods and prolonging the reservoir lifespan. In conclusion, this study proposes a proper solution to reservoir sedimentation during extreme flooding events. The optimization of water resources and economic benefits can help reservoir management achieve the goal of sustainable development. The presented research can be promoted in the worldwide reservoir to face the possibly severe sediment disaster under the threat of climate change. HIGHLIGHTS: Proper solution to the reservoir sedimentation during extreme flooding event. Optimization of water resources and economic benefit. Achievement of the reservoir sustainable development. Graphical Abstract